PELATIHAN PENGELOLAAN DAN PENCATATAN KAS KECIL DENGAN MENGGUNAKAN MICROSOFT EXCEL BERBASIS BAHASA INGGRIS - Utami, Ni Made Satya; Irwandika, Gede; Kartiningsih, Ni Luh Ratih (Jurnal Abdi Citra, 2025)
Cargo company CV. Intan Sanggraha Int'l is one of the MSMEs that serve the delivery of goods on a large scale with various delivery lines. Shipping destinations can be in the country or abroad. The COVID-19 pandemic has made the domestic and international delivery process tighter because the government is aware of the virus carried in the goods sent, so Cargo has experienced fewer sales than before. Problems that exist CV. Intan Sanggraha Int'l has not optimized the management and recording of technology-based petty cash. This community service activity aims to help CV—Intan Sanggraha Int'l by conducting training and mentoring in business management. The solution of this work program is to manage and record petty cash using Microsoft Excel software to make the recording process more efficient. This work Program is expected to benefit the community, especially companies affected by the COVID-19 pandemic, and increase company productivity.